Geothermal implications for fracture-filling hydrothermal precipitation. (November 2016) - Griffiths, L.; Heap, M.J.; Wang, F.; Daval, D.; Gilg, H.A.; Baud, P.; Schmittbuhl, J.; Genter, A.
Highlights: Hydraulic properties of fractured Buntsandstein sandstone are quantified in the laboratory. Bedding and sealed fractures affect the permeability anisotropy of the Buntsandstein. A model for the growth rate of barite crystals with temperature is proposed. Fracture permeability may be time dependant within the lifetime of a geothermal site. Abstract: In geothermal reservoirs, fluid circulation is greatly dependent on the geometry, density, and hydraulic properties of fractures. The Soultz-sous-Forêts geothermal site located in the Upper Rhine Graben in Alsace, France, consists of a granitic basement overlain by a 1.4 km-thick sedimentary succession. Core analysis and borehole wall imagery collected from reconnaissance well EPS1, drilled vertically to a depth of 2230 m, revealed an extensive fracture network throughout the granite and overlying sediments, including both open fractures and fractures sealed through mineral precipitation (primarily quartz, illite, chlorite, calcite, dolomite, barite, pyrite and galena). Here we present a combined experimental and modelling study that aims to provide insights into the permeability anisotropy in the Triassic Buntsandstein sandstone (1–1.4 km depth) and the impact of mineral precipitation. We targeted borehole samples that best represented the variability of fractures within the Buntsandstein. Forty cylindrical samples (40 mm in length and 20 mm in diameter) were prepared from the chosen borehole samples such that they contained sealed or partially-sealed fractures either parallel or perpendicular to their axis. We also prepared samples of the intact host rock. These samples were then subject to porosity and permeability measurements, and thin sections were made for Scanning Electron Microscopy (SEM) to characterise the nature of the fractures and the precipitated minerals. Permeability measurements of the Buntsandstein host rock yielded values ranging from 10 −15 m 2 to less than 10 −18 m 2 . SEM and X-ray powder diffraction analyses suggest that prevalent pore-filling illitic clays can explain the low permeability of the sandstone host rock. Additionally, we found that the permeability of fractures depends on the nature of the filling and the extent of sealing, with barite providing the most effective precipitate. Taking into account the geothermal fluid composition at Soultz-sous-Forêts, we employ a kinetic model for the barite crystal growth rate with temperature to provide an estimate for the time scale over which open fractures can seal through barite precipitation (from months to days depending on temperature). The rate increases dramatically as the temperature of the geothermal brine decreases, highlighting the risk of mineral precipitation at geothermal sites, where fluid temperature fluctuates due to circulation through the reservoir rock and fluid mixing around the injection well. An improved knowledge of the time dependency of fracture permeability will provide insights into the permeability anisotropy in the Buntsandstein and may have repercussions for the geothermal exploitation and for the ongoing fluid flow modelling of the Soultz-sous-Forêts geothermal reservoir.